Surgical Treatment of Spondylolisthesis Using Transpedicular Fixators (Eurasian Scientific Herald, 2023)
is to analyze our own results of surgical treatment of 30 patients with isthmic spondylolisthesis of the L5 vertebra, who used the method of transpedicular fixation (TPF) using various types of transpedicular constructs and methods of their installation in combination with various methods of anterior fusion.